2022
DOI: 10.3390/polym14235323
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Mechanical Properties and Bonding Properties of Flake-Zinc-Powder-Modified Epoxy Resin Composites

Abstract: As a typical brittle material, epoxy resin cannot meet its application requirements in specific fields by only considering a single toughening method. In this paper, the effects of carboxyl-terminated polybutylene adipate (CTPBA) and zinc powder on the mechanical properties, adhesion properties, thermodynamic properties and medium resistance of epoxy resin were studied. A silane coupling agent (KH-550) was used to modify zinc powder. It was found that KH-550 could significantly improve the mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…This may be because the ratio of EUR to E12 is interchangeable, and the density of polar groups is too large, so the molecular chain exhibits brittle fractures, resulting in a decrease in strength. The tensile strength and ductility of the flexible prepreg resin in this study are higher than those of toughened epoxy resins reported in many studies [ 30 , 36 , 37 , 38 ].…”
Section: Resultscontrasting
confidence: 71%
“…This may be because the ratio of EUR to E12 is interchangeable, and the density of polar groups is too large, so the molecular chain exhibits brittle fractures, resulting in a decrease in strength. The tensile strength and ductility of the flexible prepreg resin in this study are higher than those of toughened epoxy resins reported in many studies [ 30 , 36 , 37 , 38 ].…”
Section: Resultscontrasting
confidence: 71%
“…It is well known, now, that the properties of these materials depend not only on the properties of the fibers and matrices, but also on the properties of the interphase boundary between them. Primarily, these properties depend on the adhesion strength of the fibers to the matrix [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%